2016
DOI: 10.1038/srep36697
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of prenatal and perinatal risk factors in a Chinese population with reading disorder

Abstract: Several prenatal and perinatal factors have been found to be associated with developmental dyslexia (reading disorder) in alphabetic language. Given the absence of relevant studies of Chinese children, the present study tries to investigate these risk factors. A total of 45,850 students were recruited from grades three to six, from seven cities of Hubei province. Dyslexia in Chinese was diagnosed based on children’s clinical symptoms. The clinical symptoms of children’s reading performance were assessed by Dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 41 publications
4
37
0
3
Order By: Relevance
“…Although only a small sample of an ordinary school in China was used in this pilot study, the observed rates of students at risk of RD (i.e. 8 and 6% in Grades 1 and 2, respectively, Table 2) however, are in line with the hypothesis that dyslexia could be less prevalent in Mandarin-speaking communities as reported previously (Dai et al, 2016;Liu et al, 2016;Zhao et al, 2016) than in Hong Kong (9.7%) (Chan et al, 2007) where Pinyin is not used in Chinese teaching. In addition to different diagnostic criteria used, differences in education systems and special social settings for learning in Chinese populations could also explain the discrepancy in the reported prevalence of dyslexia.…”
Section: Discussionsupporting
confidence: 86%
“…Although only a small sample of an ordinary school in China was used in this pilot study, the observed rates of students at risk of RD (i.e. 8 and 6% in Grades 1 and 2, respectively, Table 2) however, are in line with the hypothesis that dyslexia could be less prevalent in Mandarin-speaking communities as reported previously (Dai et al, 2016;Liu et al, 2016;Zhao et al, 2016) than in Hong Kong (9.7%) (Chan et al, 2007) where Pinyin is not used in Chinese teaching. In addition to different diagnostic criteria used, differences in education systems and special social settings for learning in Chinese populations could also explain the discrepancy in the reported prevalence of dyslexia.…”
Section: Discussionsupporting
confidence: 86%
“…These results are in line of some studies that report disadvantages in the cognitive development of twins when compared with singletons during childhood or adulthood (Allin & Fischbein, ; Hay, O’Brien, Johnston, & Prior, ; Myrianthopoulos, Nichols, Broman, ; Record, McKeown, & Edwards, ; Tsou et al, ), and this might be attributable to both prenatal and postnatal factors. Furthermore, several studies link obstetric and neonatal variables to LDs in reading, writing, and arithmetic, such as multiple pregnancy, maternal stress, medication use, tobacco and alcohol consumption, vaginal bleeding, anesthesia, duration of labor, use of forceps, fetal presentation, placental abruption, birthweight, gestational age, perinatal asphyxia, neonatal hyperbilirubinaemia, and exposure to alcohol and other medications or certain infectious diseases such as toxoplasmosis and rubella (Cho et al, ; Chyi et al, ; Guarini et al, ; van Handel et al, ; Hokkanen, Launes, & Michelsson, ; Holm & Crosbie, ; Jain & Pandey, ; Jansson‐Verkasalo et al, ; Johnson et al, ; Kovachy, Adams, Tamaresis, & Feldman, ; Liu et al, ; Mascheretti et al, ; Morse et al, ; Roberts et al, ; Wolke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some other perinatal and obstetric factors apparently associated with school LDs are dystocia, perinatal asphyxia, neonatal hyperbilirubinaemia, and exposure to alcohol and other medications or to certain infectious diseases such as toxoplasmosis and rubella (Jain & Pandey, ; Liu et al, ; Mulas & Morant, ). Perinatal asphyxia increases the risk of reading and spelling problems in children with normal intelligence (van Handel, Swaab, de Vries, & Jongmans, ); neonatal hyperbilirubinaemia is a risk factor for reading, writing, and mathematical difficulties (Hokkanen, Launes, & Michelson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dyslexics in Chinese were diagnosed based on a set of established criteria (Liu, Wang, et al, ; Shao, Kong, et al, ). Normal readers had age‐appropriate reading abilities.…”
Section: Methodsmentioning
confidence: 99%
“…Developmental dyslexia (DD) is a neurodevelopment disorder characterized by impaired reading acquisition in spite of adequate neurological and sensorial conditions, educational opportunities, and normal intelligence (Peterson & Pennington, ). DD is the most common learning disability globally, affecting 5–17.5% school aged children learning alphabetic languages such as English (Peterson & Pennington, ), 3.45% learning logographic languages such as Chinese (Liu, Wang, et al, ), and 9.7% learning both English and Chinese in Hong Kong (Chan, Ho, Tsang, Lee, & Chung, ). Dyslexic children suffer from persistent reading disorders and also derived emotional and behavioral problems (Maughan, Rowe, Loeber, & Stouthamer‐Loeber, ).…”
Section: Introductionmentioning
confidence: 99%